Diagnostic validity of PULP (peptic ulcer perforation) score in predicting mortality in patient with operated perforated peptic ulcer in Sanglah Hospital- Denpasar - Inge Kurniawati; I Ketut Wiargitha; Tjokorda Gde Bagus Mahadewa; Bianca Jeanne (Neurologico Spinale Medico Chirurgico, 2019)
Background: Perforated peptic ulcer (PPU) is one of the most common non-traumatic emergency cases in the emergency unit, and have a high mortality rate, more than 70% in the elderly. Accurate and early identification of high-risk surgical patients with PPU is important for triage and risk stratification. The objective of this study was to evaluate the mortality in patients with operated PPU. Methods: Between January 2015 to December 2016, 50 consecutive patients with PPU who performed laparotomy were studied retrospectively. This study was a diagnostic test to evaluate the validity of PULP (Peptic Ulcer Perforation) score to predict mortality in patient with operated PPU and determine the best cut-off point. Presentation ≥ or < 24 hours, age of 65 years old, the presence of preoperative shock, ASA score, the presence of AIDS or active malignancy, liver failure, concomitant use of steroids and serum creatinine > 14.7 g/dL were evaluated in PULP score. Results: The cut-off point for PULP the score in the present study is > 7, based on the optimal cut-off value, patients could be divided into low-risk patients (a score of < 7 points), and high-risk patients (a score of > 7 points). PULP score had 91.7% sensitivity, 65.4% specificity, and 78% accuracy in this study. Positive predictive value and negative predictive the values were 71% and 89.9%. Conclusion: The PULP score is sensitive to predict the mortality risk in patients operated for perforated peptic ulcer and can assist in risk stratification and triage.